Conservation Status of the Indian Peafowl Pavo cristatus (Aves: Galliformes: Phasianidae) in Bangalore University Campus, Bengaluru, Karnataka, India - Rajashekara, S.; Ananda, N.; Amulya, S.; Bhagyashree, M.; Khanam, Najma; Prathibha, Y.; Imraz, Shahista; Sowmyashree, R.S.; Hamsa Rekha, V.; Vijayalakshmi, D. S.; Venkatesha, M. G. (Indian Forester, 2019)
The Indian Peafowl, Pavo cristatus was abundant in Bangalore University Campus (BUC) during 1970-80. However, the peafowl population declined alarmingly in the BUC region after 1990. The present paper deals with the abundance, sex ratio of peafowls and their conservation methods in the Biodiversity Park (Bio-Park) of BUC, which had been established in 2006. A total of 117 peafowls was recorded in the BUC region in which the females outnumbered the males. The increased abundance of the peafowl population in the campus could be mainly due to the availability of suitable roosting, foraging and nesting sites. The peafowls have used 18 species of plants and trees for perching and roosting in BUC. The peafowl population increased in the BUC region due to habitat rejuvenation and protection, availability of food sources and breeding/nesting sites. The results of the present investigation constitute the baseline data for the further understanding of the ecological community of national bird in the protected habitats as hotspots for biodiversity of urban ecosystem. Conservation of microhabitats through the proper restoration of ponds, streams and water check-dams including vegetation in the BUC is responsible for the existence of peafowl population.